(3aVGFd ehdO GdfHj Udi Gddg Ydjg hSdes - (3GdbQTj GdJjej GdHcQj GdMfHdj, CHh GdaQL, GHf GdLhRj, LeGd GdOjf, YHO GdQMef Hf Ydj Hf eMeO, (B597 (3g`s ((3UGdM GdcGTas)
(3ChdgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde ef YXe ehdOj cfJ dg TajYG jhe GdbjGeI hef Cfab OQgeG Ydi ehdOj acCfeG Cfab LHdG ef PgH CMeQ aj SHjd Gddgs
(3BNQgG (B:s
(3bGd dgG(B: (3GdPj CQSd Edjc CQSd Edj aCSdeG hMSf ESdGegeG HHQcI ehdO GdfHj Udi Gddg Ydjg hSde hgPG gh ehdO GdfHjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B3 / 316s
(3eYLe GdeDdajf(B: (3L(B2 / 100s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs